Effect of different types of static mixer geometry on quality of microbubble generation / Tee Wu Yang - Tee , Wu Yang (2020)
This research project is mainly focused on the impact of different types of static mixer on the quality of microbubble generation. The design of the microbubble generation consists of venturi to allow the air intake by using pressure difference and then different static mixer geometry are tested to investigate the effect on bubble rising time and dissolved oxygen (DO). At the first part of study, the work comprises of the relationship of bubble rising time at different pressures and bubble diameter at different pressures. It has proved that higher pressure will induce small bubble diameter and the bubble rising time increases when pressure applied is increasing. Moreover, the factors that influences dissolve oxygen (DO) are studied as well. It is known that longer bubble rising time will have greater DO as the bubble rising time is a representation of bubble diameter. Therefore, it has recorded that the DO surged up by 40% when the diameter of bubble is reduced by 12% in this study. Also, the implementation of different types of static mixer geometry has significant improvement in DO and smaller bubbles are generated. The result is obvious when static glass marbles are used together with static mixer. The DO has been improved by around 10% when 2-phase marbles are applied together with static mixer compared to case with static mixer only. This is a result as greater bubble shredding in turbulence flow is found when multiple static mixers with different geometry are added into the system.